2020
DOI: 10.1371/journal.pone.0229597
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prognostic nutritional index as an independent prognostic factor for resected ampulla of Vater cancer

Abstract: Introduction Prognostic nutritional index (PNI) reflects the nutritional and immunologic status of the patients. The clinical application of PNI is already well-known in various kinds of solid tumors. However, there is no study investigating the relationship between PNI and oncological outcome of the resected ampulla of Vater (AoV) cancer. Materials and methods From January 2005 to December 2012, the medical records of patients who underwent pancreaticoduodenectomy for pathologically confirmed AoV cancer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In previous reports, factors predicting survival among patients with AVC included tumor node metastasis (TNM) stage, resection margin, lymph node metastasis (LNM), vascular invasion, perineural involvement, differentiation grade, and perioperative nutritional status [5][6][7][8][9]. Although the effects of recurrence on postoperative mortality have been well studied in patients with periampullary cancers, such as pancreatic and distal bile duct cancers, there are few analyses of its impact on AVC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, factors predicting survival among patients with AVC included tumor node metastasis (TNM) stage, resection margin, lymph node metastasis (LNM), vascular invasion, perineural involvement, differentiation grade, and perioperative nutritional status [5][6][7][8][9]. Although the effects of recurrence on postoperative mortality have been well studied in patients with periampullary cancers, such as pancreatic and distal bile duct cancers, there are few analyses of its impact on AVC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI) is a marker of nutritional status and systemic inflammation, based on serum albumin concentration and total lymphocyte count, both of which can be easily obtained from routine preoperative blood tests [6]. Several studies [7][8][9][10][11] have shown that the PNI can be used as a prognostic marker in patients with various cancers. However, few studies have evaluated the prognostic value of the PNI in patients with BTC.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable features are its low oxygen, low pH and high pressure. More and more researches indicate systemic nutrition has been found to be a crucial ingredient of the tumor microenvironment that plays remarkable roles in tumor growth, progression and metastasis 2 . For patients with malignant tumors, the tumor itself will consume a lot of protein, causing damage to tissue structure and organ functions; in addition, gastrointestinal obstruction caused by digestive organ tumors can lead to loss of appetite, nausea, vomiting, diarrhea which is also associated with poor nutrition and immunosuppression 3 5 .…”
Section: Introductionmentioning
confidence: 99%